Implementation and investigation of mode locking in GaN‐based laser diodes in external cavity configuration. Issue 5 (30th December 2014) - Weig, Thomas; Höck, Helge; Holc, Katarzyna; Köhler, Klaus; Wagner, Joachim; Schwarz, Ulrich T.
<x xml:space="preserve">Abstract</x> Investigation of spectro‐temporal characteristics of short‐pulse generation from a violet–blue AlGaInN multi‐section laser diode implemented in an external cavity is demonstrated. The front facet is coated with a single layer of anti‐reflection coating, resulting in superluminescent diodes with a broad spectrum. The coated diode is placed in an external cavity in Littrow configuration for wavelength‐tuning, and in Littman–Metcalf configuration for ultrashort pulse generation. We report on fundamental, harmonic, as well as hybrid mode locking. Compensating for the group velocity dispersion, we compress the pulse duration down to 2 ps, which is at the resolution limit of the streak camera. Mode locking and sub‐ps pulse generation are hindered by the photon density‐induced gain saturation, manifested as mode competition and mode clustering superimposed with mode locking. We show, that hybrid mode locking can suppress the mode competition successfully.